Distance course examination - Vladimir Kukharenko; Bohdan Shunevych; Hennadiy Kravtsov (Academy of Cognitive and Natural Sciences, 2022)
The article deals with the theoretical foundations of carrying out distance course (DC) examination with the aim of creating the program for expert training. An expert is defined as a specialist who has experience in compiling distance courses, organization of distance learning as well as has and uses content tutor skills. The article also describes the basic skills that an expert should have as well as typical mistakes of the developers of distance courses are presented. On the basis of the research a DC ``Expert examination of distance course'' was compiled for experienced developers of distance courses and administrators of distance learning systems at different institutions. During the training, the learners analyzed the purpose of Bloom's taxonomy and its accessibility, the complexity of the text and its design, the tasks and learning activities, the quality of tests and the evaluation system, etc. The result of the course training is learner's report on the distance course examination and analysis of this work. 47 lecturers of Ukrainian educational institutions were trained and only 12 of them successfully completed the training.